Recovery-adaptation - Sands, W. A.; Apostolopoulos, N.; Kavanaugh, A. A.; Stone, M. H. (Strength and Conditioning Journal, 2016)
Athlete training should proceed from thorough and systematic periodized plans for the implementation of training loads. The time-course of training should include periods of high loads punctuated by reduced loads and rest. As there are a wide variety of means and methods used for the implementation of loads, there are numerous means and methods for enhancing recovery and adaptation (ra). Ra from athlete training are poorly understood and in need of a model or framework to advance our ability to systematically complement training with appropriate modalities.